THE FUNCTION OF SYMBOLISM IN POETRY (IN THE EXAMPLE OF "THE WASTE LAND" BY T.S. ELIOT) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
The Waste Land is a highly symbolic poem that captures the disillusionment and fragmentation of the early 20th century, particularly in the aftermath of World War I. Through intricate symbolism, Eliot explores themes of spiritual desolation, cultural decay, and the loss of meaning in the modern world. The poem is fragmented in both structure and content, reflecting the chaotic, disjointed experience of modern life. Key symbols in the poem include the waste land itself, which serves as a metaphor for spiritual emptiness and cultural decline, and the imagery of water and drought, symbolizing both renewal and deprivation. Fire, tarot cards, and the Fisher King are other powerful symbols used to convey destruction, the search for meaning, and the deep wound of contemporary humanity. These symbols are drawn from a wide range of sources, including mythology, religion, literature, and history, which Eliot employs to create a richly textured landscape that is both ancient and modern.